Project approach as a tool for the implementation of national projects in Russia - N. V. Kuznetsov; T. A. Pershina (Модернизация, инновация, развитие, 2023)
Purpose:  of the presented research is to evaluate various methods of project management, including methodological approaches already used in our country, for their application in the implementation of national projects of the Russian Federation.Methods: the work used traditional methods of scientific theoretical analysis, including system analysis, as well as an induction approach.Results: the authors consider the historical aspect of the formation of the project approach as a method used in the professional field of management. In the work, various management approaches presented by different countries were studied and systematized. The analysis of project management experience in the leading countries of the world, as well as in the Russian Federation, was carried out. The study presents the use of the project approach in the implementation of national projects, an assessment of the work of the project implementation monitoring system is given. Based on the identified methodological and organizational problems in the formation of new and implementation of current national projects in Russia, the authors conclude that it is necessary to improve project management methods and monitoring the achievement of performance indicators of national projects.Conclusions and Relevance:  the specifics of public administration in Russia require the development of their own design methods in the management system, which will only rely on those already created in the world, but not copy them completely. So, according to the authors, the best practice will be the use of flexible management methods. Existing methodologies and individual strategies of other countries can only help in developing ideas for both the general concept of the implementation of existing national projects and for designing new ones.